Natural history of native artiodactyls of the Upper Paraguay Basin with annotations on taxonomy, distribution, abundance, ecology, and conservation - Keuroghlian, Alexine; Hofmann, Gabriel Selbach; Andrade, Bruna da Silva; Tiepolo, Liliani Marilia; Oliveira, Maxwell da Rosa; Camilo, André Restel; Tomas, Walfrido Moraes (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
We present a review of the different aspects related to native artiodactyl mammals from the Upper Paraguay Basin (UPB) and Brazilian Pantanal Basin and highlands, represented by two species from the Tayassuidae family (Tayassu pecari and Pecari tajacu) and four from the Cervidae family (Blastocerus dichotomus, Mazama americana, Mazama gouazoubira, and Ozotoceros bezoarticus). Originally these six species had a wide geographic distribution, but currently, some of them are globally or regionally threatened. However, unlike the deforested Pantanal highlands, the Pantanal basin still maintains healthy populations of these species, making it an ideal area for research and their conservation in this dynamic heterogeneous environment. In this review, we compiled and synthesized the main information related to their natural history, morphology, taxonomy, population structure, ecology and conservation. We prioritized data generated by studies conducted in different regions of the UPB. For comparative purposes, we also include data from neighboring ecoregions. We hope that this review contributes information on these Brazilian species and ultimately contributes to public policies that implement conservation strategies for the long-term conservation of native neotropical peccaries and deer.
Keywords: Tayassu pecari; Pecari tajacu; Blastocerus dichotomus; Mazama americana; Mazama gouazoubira; Ozotoceros bezoarticus